Factors Influencing Consumer Behavioral Intention to Use Food Delivery Services: A Study of Foodpanda - Dwi Nita Aryani; Padmalini Singh; Yun Xuan Khor; Daisy Mui Hung Kee; Kornelia Selvia; Cui Wen Lee; Yee Hsien Lee; Levisha Anantharavoo (AIBPM Publisher, 2022)
With the advancement of technology in this 21st century, food delivery services have emerged as a new wave in the food and beverage industry. People can now order the food with a simple click of a button. This study analyzes the factors influencing consumers’ behavioral intention to use the food delivery apps-Foodpanda. Both primary and secondary data were collected through various sources. An online survey form was prepared to collect information from 100 respondents. The results indicated that factors including price, information quality and the perceived usefulness of the Foodpanda application have significant influences toward the consumer behavioral intention to use the food delivery service.